Sunflower Car Rental / Norliana Husin... [et al.] - Husin, Norliani; Said, Hasanah; Abu Bakar, Zuraidah; Ali, Suriyati (2001)
Sunflower Car Rental is a new business that provides car for rent. The car is suitable for any activities like tour and businesses. It’s also suitable for individuals, family and group. This business operates is Lim Lean Teng Mansion, (Infront of eastern & Oriental hotel) Farquhar Street 10200 Penang.